Domestic accidents among under-5 year children: a study on the modern day epidemic - Khan, Samreen; Tauheed, Nazia; Nawab, Sana; Afzal, Suboohi; Khalique, Najam (International Journal Of Community Medicine And Public Health, 2019)
Background: Domestic accidents are a priority problem, and urgent attention is required to prevent considerable morbidity and mortality in children of the under-five age group. Methods: Community based cross-section study done in the peri-urban areas of Aligarh, India. Mothers/care-givers were interviewed about any domestic accident faced by children under 5 year age, in the last 1 year, through a semi-structured, pilot tested questionnaire. Multivariable logistic regression was performed using SPSS 24.0 software. Results: Majority of respondents were in the age group 20-35 years, majority of the children affected were male (35.6%), and in the age group of 3 to <4 years (22.3%). Most accidents occurred inside home, most commonly due to falls, followed by sharp injury and burn. Mother’s education level had a significant association with the occurrence of domestic accidents (odd’s ratio: 2.34, CI: 1.08-5.07). Conclusions: Domestic accidents among children are prevalent in the study area. Dissemination of injury prevention information with special focus on household modification and increased parental supervision are effective strategies to prevent unintentional injury.